Banana inflorescence: Its bio-prospects as an ingredient for functional foods - Beng, Fye Lau; Kin, Weng Kong; Kok, Hoong Leong; Sun, Jian; He, Xuemei; Wang, Zhenxing; Mustafa, Mohd Rais; Tau, Chuan Ling; Ismail, Amin (Elsevier, 2020)
Background: There is a renewed interest in the utilisation of agricultural by-products, particularly those from crop plants, as a source of functional ingredients. The banana (Musa spp.) is a popular food crop worldwide but its inflorescence is often undervalued, similar to other agricultural by-products. As the banana inflorescence is traditionally consumed as food and medicine, it has the potential to be developed into functional foods. Scope and approach: The present review systematically summarises the nutritional attributes, bioactive components and potential health-promoting properties of the inflorescence of the banana plant for the first time. Key Findings and Conclusions: The findings thus far, particularly on the broad array of bioactive chemical constituents in the inflorescence and their corresponding biological activities, seem to justify its proposed use in various food industries. Perspectives on the current status of research and future work potentially leading to the development and commercialisation of the banana inflorescence into value-added products, are also provided. From this review, it is clear that the banana inflorescence has great potential to be developed into useful nutraceuticals and functional foods.